Analisis Efektivitas Live Streaming “PVN Shoes” pada E-Commerce - Prakasta Karisma Putra; Terrylina Arvinta Monoarfa; Meta Bara Berutu (Univiversitas Dr. Djar Wattiheluw, 2025)
This study aims to evaluate the effectiveness of